2015
DOI: 10.18632/oncotarget.5147
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of the mutations in BAP1, PBRM1 and SETD2 genes reveals the impaired molecular processes in renal cell carcinoma

Abstract: Clear cell Renal Cell Carcinoma (ccRCC) is due to loss of von Hippel–Lindau (VHL) gene and at least one out of three chromatin regulating genes BRCA1-associated protein-1 (BAP1), Polybromo-1 (PBRM1) and Set domain-containing 2 (SETD2). More than 350, 700 and 500 mutations are known respectively for BAP1, PBRM1 and SETD2 genes. Each variation damages these genes with different severity levels. Unfortunately for most of these mutations the molecular effect is unknown, so precluding a severity classification. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
16
1
1
Order By: Relevance
“…ccRCC patients can show different clinical manifestation and treatment response because of the tumor heterogeneity in histology, oncogenicity and molecular alterations in tumor suppressor genes [ 24 ]. Furthermore, previous reports have shown that the mutations on Von Hippel-Lindau ( VHL ), Polybromo-1 ( PBRM1 ) and BRCA1 associated protein-1 ( BAP1 ) are the most common somatic mutations in ccRCC which induces the occurrence and development of ccRCC [ 25 ]. In this study, we found that LOC653786 was upregulated in ccRCC tissues compared to normal tissues by analyzing TCGA data, but it is unclear whether the higher level of LOC653786 in ccRCC tissues was associated with the mutations of VHL, BAP1 and PBRM1 .…”
Section: Discussionmentioning
confidence: 99%
“…ccRCC patients can show different clinical manifestation and treatment response because of the tumor heterogeneity in histology, oncogenicity and molecular alterations in tumor suppressor genes [ 24 ]. Furthermore, previous reports have shown that the mutations on Von Hippel-Lindau ( VHL ), Polybromo-1 ( PBRM1 ) and BRCA1 associated protein-1 ( BAP1 ) are the most common somatic mutations in ccRCC which induces the occurrence and development of ccRCC [ 25 ]. In this study, we found that LOC653786 was upregulated in ccRCC tissues compared to normal tissues by analyzing TCGA data, but it is unclear whether the higher level of LOC653786 in ccRCC tissues was associated with the mutations of VHL, BAP1 and PBRM1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, germline BAP1 mutations are associated with more aggressive UM [6]. BAP1 also plays a prognostic role in other cancers such as RCC and cholangiocarcinoma [79].…”
Section: Introductionmentioning
confidence: 99%
“…A predominant role in kidney cancer is played by inactivation of Von Hippen Lindau (VHL) tumor suppressor gene with consequent increased cellular amount of Hypoxia-Inducible Factor-1 alpha (HIF-1a) that cause abnormal cellular growth and angiogenesis [24]. Therefore inhibition of angiogenesis represents the mainstay of treatment of metastatic RCC [5, 6].…”
Section: Introductionmentioning
confidence: 99%